The Role of Digital Competence for Pre-Service Teachers in Higher Education Indonesia - Hengki Muhammad Akbar; Biyanto Biyanto (STAI Hubbulwathan Duri, 2022)
Progress in the digital era has accelerated in the past few years, including its impact on education, which must prepare competent human resources. Teachers are expected to have competencies that can meet the demands of the times. This study aims to describe the role of digital competence on pre-service teachers in Indonesia. Using the Systematic Literature Review (SLR), this article examines the results of research related to Digital Competence which raises the subject of students taking education department in Indonesia. The literature review was obtained from the “lens.org”, ”scholar.google.com”, “eric.ed.gov” “link.springer.com”, and ”sciencedirect.com” websites using the keyword “kompetensi digital” and “digital competence” with filter for the 2015-2021 years range. After that, it is filtered with the open-access journal option and language restrictions in English and Indonesian. The analysis is based on research objectives that support providing an overview of the role of digital competence in pre-service teachers from selected articles. After being reviewed through inclusion and exclusion criteria evaluated by quality assessments, five articles published are analysed. The result shows that digital competence plays a role in being an indicator in measuring literacy levels, improving pre-service teacher's learning outcomes, and contributing to the teaching process.